Role of granulocytes in the induction of an experimental endocarditis with a dextran-producing Streptococcus sanguis and its dextran-negative mutant. - Meddens, M. J. (1984)
The role of granulocytes in the induction of endocarditis with a dextran-producing Streptococcus sanguis and a dextran-negative mutant of this strain was studied. The number of colony-forming units of Streptococcus sanguis needed to colonize the vegetations in 50% of the rabbits (ID50) was significantly lower for the parent strain than for the dextran-negative mutant. However, in granulocytopenic rabbits the ID50s of both strains did not differ measurably. Dextran-negative streptococci were more readily cleared from the circulation than dextran-positive, but in this respect no difference was found between control and granulocytopenic rabbits, which indicates that clearance cannot account for the difference in ID50 between the two strains in the control group. At serum concentrations of 5% and lower, in-vitro granulocytes phagocytosed the dextran-negative streptococci more rapidly than the dextran-positive. The intracellular killing of the streptococci was no influenced by dextran production. This study suggests that an impaired phagocytic removal of attached bacteria from the vegetational surface can be a factor promoting the induction of endocarditis by dextran-producing streptococci.